Semantics of compounding - Hacken, Pius ten, ed
"The question of how to determine the meaning of compounds was prominent in early generative morphology, but lost importance after the late 1970s. In the past decade, it has been revived by the emergence of a number of frameworks that are better suited to studying this question than earlier ones. In this book, three frameworks for studying the semantics of compounding are presented by their initiators: Jackendoff's Parallel Architecture, Lieber's theory of lexical semantics, and Štekauer's onomasiological theory. Common to these presentations is a focus on English noun-noun compounds. In the following chapters, these theories are then applied to different types of compounding (phrasal, A+N, neoclassical) and other languages (French, German, Swedish, Greek). Finally, a comparison highlights how each framework offers particular insight into the meaning of compounds. An exciting new contribution to the field, this book will be of interest to morphologists, semanticists and cognitive linguists"--